Iron(III) Azadiphenolate Compounds in a New Family of Spin Crossover Iron(II)–Iron(III) Mixed-Valent Complexes - Wasinee Phonsri (Magnetochemistry, 2019)
A new family of mixed valent, double salt spin crossover compounds containing anionic FeIII and cationic FeII compounds i.e., [FeII{(pz)3CH}2][FeIII(azp)2]2·2H2O (4), [FeII(TPPZ)2][FeIII(azp)2]2]·H2O (5) and [FeII(TPPZ)2][FeIII(azp)2]2]·H2O·3MeCN (6) (where (pz)3CH = tris-pyrazolylmethane, TPPZ = 2,3,5,6, tetrapyridylpyrazine and azp2− = azadiphenolato) has been synthesized and characterised. This is the first time that the rare anionic spin crossover species, [FeIII(azp)2]−, has been used as an anionic component in double salts complexes. Single crystal structures and magnetic studies showed that compound 6 exhibits a spin transition relating to one of the FeIII centres of the constituent FeII and FeIII sites. Crystal structures of the anionic and cationic precursor complexes were also analysed and compared to the double salt products thus providing a clearer picture for future crystal design in double spin crossover materials. We discuss the effects that the solvent and counterion had on the crystal packing and spin crossover properties.